Fulminant myocarditis after the second dose of COVID‐19 mRNA vaccination. Issue 2 (7th February 2022) - Oka, Akihiro; Sudo, Yuya; Miyoshi, Toru; Ozaki, Masatomo; Kimura, Yuta; Takagi, Wataru; Ugawa, Satoko; Okada, Tomoaki; Nosaka, Kazumasa; Doi, Masayuki
Abstract: Myocarditis is an adverse event associated with coronavirus disease 2019 (COVID‐19) mRNA vaccination. A 50‐year‐old man presented with dyspnea and resting chest pain after receiving the second dose of the COVID‐19 mRNA vaccine and developed cardiogenic shock. Fulminant myocarditis was diagnosed by endomyocardial biopsy and treated with intravenous corticosteroids. Abstract : Fulminant myocarditis is an adverse event associated with the COVID‐19 mRNA vaccination. Steroid pulse therapy may control the pathology of myocarditis caused by COVID‐19 mRNA vaccination.